Reporter gene assay for the quantification of the activity and neutralizing antibody response to TNFα antagonists. - Lallemand, C; Kavrochorianou, N; Steenholdt, C; Bendtzen, K; Ainsworth, M; Meritet, J; Blanchard, B; Lebon, P; Taylor, P; Charles, P; Alzabin, S; Tovey, MG (2011)
A cell-based assay has been developed for the quantification of the activity of TNFα antagonists based on human erythroleukemic K562 cells transfected with a NFκB regulated firefly luciferase reporter-gene construct. Both drug activity and anti-drug neutralizing antibodies can be quantified with a high degree of precision within 2h, and without interference from cytokines and other factors known to activate NFκB. The assay cells also contain the Renilla luciferase reporter gene under the control of a constitutive promoter that allows TNFα-induced firefly luciferase activity to be normalized relative to Renilla luciferase expression. Thus, results are independent of cell number or differences in cell viability, resulting in intra and inter assay coefficients of variation of 10% or less. Normalization of results relative to the expression of an internal standard also provides a means for correcting for serum matrix effects and allows residual drug levels or anti-drug neutralizing antibodies to be quantified even in serum samples with a relatively high degree of cytotoxicity.